English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

7 answers

Equation of line : y=mx + c
Gradient = (-5-0)/(-3-3)
= 5/6

Thus y=(5/6)x + c

Sub. in Point (3, 0)

0= (5/6)(3) + c
c= (-5/2)

thus the line is y = (5/6)x - (5/2)

2006-09-04 20:54:11 · answer #1 · answered by maczh2002 2 · 0 0

First, we need the slope. This is given by m = dy/dx. dy = 0 - -5, or 5; dx = 3 - -3 or 6. So, in the straight line equation y = mx + c, we have m = 5/6. It is convenient to use the second point to determine c: 0 = (5/6)3 + c, so c is obviously -2.5. The complete equation is then
y = (5/6)x - 2.5. Checking, we have:
-5 = (5/6) -3 - 2.5 -- OK;
0 = (5/6) 3 - 2.5 -- OK. We're done.

2006-09-05 04:01:03 · answer #2 · answered by Anonymous · 0 0

Well... let it be a*x+b=y the equation of the line, where a, b real numbers. Then, if the line passes through the spots (-3,-5) and (3,0), this equation should be true for these pairs of (x,y). So, you must solve the sustem:
a*(-3)+b=-5
a*3+b=0
That is equal to:
b=a*(-3)
a*(-3)+a*(-3)=-5
That means:
a*(-6)=-5
b=a*(-3)
And the solution is:
a=5/6
b=-3*5/6=-5/2
So nthe equation of the line passing through the spots (-3,-5) and (3,0) is: y=(5/6)*x-5/2.

2006-09-05 04:02:38 · answer #3 · answered by Leonidas Nikolakis 3 · 0 0

-5-0
m= -------- =5/6 so the line would be:
-3-3
y-0 = 5/6 (x - 3 ) so :
y = 5/6 x -5/2

2006-09-05 05:50:17 · answer #4 · answered by Sarah 2 · 0 0

It is (x+3)/(y+5)=(-3-3)/(-5), which simplifies to:

5x-6y-15=0

2006-09-05 03:56:05 · answer #5 · answered by Anonymous · 0 0

y=5/6x+-3

or

y=5/6x-3

I didn't get it that well on the y-intercept.

2006-09-09 01:25:10 · answer #6 · answered by _anonymous_ 4 · 0 0

yup..thts guy's method is correct though i didnt check the calculations..

2006-09-05 03:57:02 · answer #7 · answered by Anonymous · 0 0

fedest.com, questions and answers